Comparison of serum concentrations of humanin in women with and without gestational diabetes mellitus. (2nd December 2018) - Ma, Yuhang; Li, Shumei; Wei, Xiaohui; Huang, Jingjing; Lai, Mengyu; Wang, Nian; Huang, Qianfang; Zhao, Li; Peng, Yongde; Wang, Yufan
Abstract: Humanin (MT-RNR2) is an endogenous polypeptide that is involved in many diseases, including T2DM. Gestational diabetes mellitus (GDM) is defined as hyperglycemia during pregnancy. The aim of this study was to evaluate serum humanin levels in women with or without GDM and to elucidate possible correlations with anthropometric parameters, metabolic parameters and the incidence of GDM. Eighty-four women with GDM and 73 control women were enrolled in this study. The clinical and biochemical parameters of all subjects were determined. Serum humanin levels were measured by an ELISA. Serum humanin levels were significantly lower in women with GDM than in control women. Moreover, humanin levels were significantly negatively correlated with the presence of GDM, body weight, BMI at 24 weeks of gestation, TG, FPG, 1 hPG, 2 hPG, FINS, and HOMA-IR. In contrast, humanin levels were significantly positively correlated with FT3 and FT4. A binary logistic analysis showed that humanin levels were associated with the incidence of GDM. Additional follow-up studies are needed to highlight whether and how decreased humanin levels play an important role in GDM. 摘要: Humanin (MT-RNR2)是一种内源性多肽, 与很多疾病相关, 包括2 型糖尿病。 妊娠期糖尿病（GDM）是指在妊娠期的血糖异常升高。本研究的目的就是比较血清humanin多肽在患和不患妊娠期糖尿病女性之间的差别, 并阐明humanin多肽与人体某些参数, 代谢指标及GDM发生率之间可能存在的相关性。84名GDM女性与73名正常妊娠女性纳入该研究。记录所有患者的临床及生物代谢指标, 血清humanin多肽水平用ELISA方法检测。结果显示, GDM患者中humanin多肽的水平显著低于对照组, humanin多肽的水平与GDM发生率、体重及妊娠24周时BMI、甘油三酯、空腹血糖、1小时空腹血糖, 2小时空腹血糖、胰岛素及胰岛素抵抗指数之间存在显著的负相关。相反, humanin多肽的水平与FT3和 FT4呈显著的正相关。二元的Logistic回归分析显示humanin多肽水平与GDM的发生率相关。尚需要进一步的研究来证实humanin多肽水平的降低是否在GDM的发生中起着重要的作用, 又是如何起作用的。